Accounting and financial management of village fund allocation (Empirical Study in Medaeng Village, Waru District, Sidoarjo Regency) - Iga Vidya Marvanti (Indonesia Auditing Research Journal, 2023)
This research aims to determine the application of accounting and financial management of Village Fund Allocations, the mechanism for disbursing Village Fund Allocations, the stages of preparing Village Fund Allocation financial management, the obstacles encountered in implementing accounting and financial management of Village Fund Allocations, and the efforts made in overcoming obstacles that occurs in the application of accounting and financial management of Village Fund Allocation in Medaeng Village, Waru District, Sidoarjo Regency. This research is a descriptive study using a qualitative approach. Sources of data used are primary data and secondary data. Data collection techniques include observation, interviews, library research, and documentation. The results of data collection were analyzed using a comparative qualitative descriptive method. The results showed that the village fund allocation financial accounting system used was by using the Microsoft Excel program in the form of a General Cash Book and Cash Book for Receipt Assistance and Expenditure Assistance Cash Book. As for Financial Management, Village Fund Allocations in 2015 are quite good and realistic because they have been arranged in the Budget Plan (RAB). Where one of the Village Income sources is obtained in the form of Village Fund Allocation which is used for fixed income and village apparatus allowances, office operations including consumables, office services, motor vehicle maintenance, printing and duplication, meeting food and drinks, and management honorarium finance, BPD allowances,